Deoxycytidine and Deoxythymidine Treatment for Thymidine Kinase 2 Deficiency. Issue 5 (4th May 2017) - Lopez‐Gomez, Carlos; Levy, Rebecca J.; Sanchez‐Quintero, Maria J.; Juanola‐Falgarona, Martí; Barca, Emanuele; Garcia‐Diaz, Beatriz; Tadesse, Saba; Garone, Caterina; Hirano, Michio
Abstract : Objective: Thymidine kinase 2 (TK2), a critical enzyme in the mitochondrial pyrimidine salvage pathway, is essential for mitochondrial DNA (mtDNA) maintenance. Mutations in the nuclear gene, TK2, cause TK2 deficiency, which manifests predominantly in children as myopathy with mtDNA depletion. Molecular bypass therapy with the TK2 products, deoxycytidine monophosphate (dCMP) and deoxythymidine monophosphate (dTMP), prolongs the life span of Tk2‐deficient (Tk2 –/– ) mice by 2‐ to 3‐fold. Because we observed rapid catabolism of the deoxynucleoside monophosphates to deoxythymidine (dT) and deoxycytidine (dC), we hypothesized that: (1) deoxynucleosides might be the major active agents and (2) inhibition of deoxycytidine deamination might enhance dTMP+dCMP therapy. Methods: To test these hypotheses, we assessed two therapies in Tk2 –/– mice: (1) dT+dC and (2) coadministration of the deaminase inhibitor, tetrahydrouridine (THU), with dTMP+dCMP. Results: We observed that dC+dT delayed disease onset, prolonged life span of Tk2‐deficient mice and restored mtDNA copy number as well as respiratory chain enzyme activities and levels. In contrast, dCMP+dTMP+THU therapy decreased life span of Tk2 –/– animals compared to dCMP+dTMP. Interpretation: Our studies demonstrate that deoxynucleoside substrate enhancement is a novel therapy, which may ameliorate TK2 deficiency in patients. Ann Neurol 2017;81:641–652